2014
DOI: 10.1159/000358583
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Self-Reported versus Hospital-Coded Diagnosis of Stroke: A Cross-Sectional and Longitudinal Study

Abstract: Background: Population-based studies, as well as clinicians, often rely on self-report and hospital records to obtain a history of stroke. This study aimed to compare the validity of the diagnosis of stroke by self-report and by hospital coding according to their cross-sectional association with prevalent vascular risk factors, and longitudinal association with recurrent stroke and major cardiovascular outcomes in a large cohort of older Australian men. Methods: Between 1996 and 1999, 11,745 older men were sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 19 publications
(27 reference statements)
2
18
0
Order By: Relevance
“…Additionally, the self-report nature of the study may lend itself to social desirability and recall bias. However, high validity in self-report CVD-related factors has been documented in the literature [31][32][33]. For example, a study of low-income women indicated selfreport levels for high BMI, hypercholesterolemia, and hypertension were associated with clinical measures [34].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the self-report nature of the study may lend itself to social desirability and recall bias. However, high validity in self-report CVD-related factors has been documented in the literature [31][32][33]. For example, a study of low-income women indicated selfreport levels for high BMI, hypercholesterolemia, and hypertension were associated with clinical measures [34].…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of the health impacts during high summer heat was developed as a proxy variable for the perceived overall state of health in a heat context. The validity of self-reported versus medical-based diagnoses and behaviours has been well established over time, several countries and data collection methods, especially as a tool for predicting future risks and as an epidemiologic survey tool for prevention and public health actions (Fahimi et al 2008;Jamrozik et al 2014;Pierannunzi et al 2013;Starr et al 1999). The risk group consisted here of respondents saying that they felt (moderately or greatly) the harmful health effects of heat when it was very hot and very humid during the summer (vs. slightly or not at all).…”
Section: Criterion-related Validity Of the Indexmentioning
confidence: 99%
“…Given the case-fatality rates at 1 month between 10 and 25% [1] and the rising incidence in people younger than 55 years [1,2], dedicated care networks are necessary to limit the adverse consequences of stroke [3] . Reliable estimates of the stroke burden at the national level are required to establish efficient health policies [4,5].…”
Section: Introductionmentioning
confidence: 99%